2021
DOI: 10.1111/jpn.13486
|View full text |Cite
|
Sign up to set email alerts
|

Response of meat chickens to different sources of arginine in low‐protein diets

Abstract: Arginine activity in broiler diets can be supplied by L‐arginine (Arg), guanidinoacetic acid (GAA) and L‐citrulline (Cit), all of which are commercially available. This study was conducted to assess the effects of Arg source and level on broiler performance, nutrient digestibility and carcass parameters. Day‐old Ross 308 cockerels (n = 768) were assigned to one of eight dietary treatments using a completely randomized design: normal protein (NP), low protein deficient in Arg (LP) and LP with two levels of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…When Arg was added back to the Arg deficient low CP diet, weight gain, feed efficiency, breast meat yield, and breast meat Cr concentration increased, abdominal fat pad decreased and became comparable to the normal CP treatment. Some of these results are in line with the recent findings ( Dilger et al., 2013 ; Dao et al., 2021 ) and highlight the importance of supplemental Arg in a low CP diet fed to broilers as described above. Although the addition of Arg to the Arg deficient low CP diet had no significant effect on wooden breast and white striping issues, Bodle et al.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…When Arg was added back to the Arg deficient low CP diet, weight gain, feed efficiency, breast meat yield, and breast meat Cr concentration increased, abdominal fat pad decreased and became comparable to the normal CP treatment. Some of these results are in line with the recent findings ( Dilger et al., 2013 ; Dao et al., 2021 ) and highlight the importance of supplemental Arg in a low CP diet fed to broilers as described above. Although the addition of Arg to the Arg deficient low CP diet had no significant effect on wooden breast and white striping issues, Bodle et al.…”
Section: Discussionsupporting
confidence: 90%
“…During 10 to 42 d, the birds offered 15 g/kg low CP Arg deficient diet had 7.8% lower weight gain, 10 points higher FCR, 8.5% lower breast meat yield, 30.4% more abdominal fat pad and 27.2% lower Cr concentration in breast meat compared to those offered a normal CP diet. Some of these observations are in line with the recent findings ( Dilger et al., 2013 ; Castro et al., 2019 ; Dao et al., 2021 ) and highlight the negative effects of Arg deficiency in broilers. Arginine deficiency also increased breast meat pH which may favor microorganism growth and decrease the shelf life of breast meat.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In broilers, Cit has been shown to have Arg-sparing effects ( Klose and Almquist, 1940 ; Tamir and Ratner, 1963 ; Su and Austic, 1999 ); however, information on the effects of Cit supplementation on growth performance and other parameters is extremely limited. A recent study by Dao et al. (2020) indicated that supplementation of Cit to an Arg-deficient reduced protein diet for broilers resulted in similar growth performance, carcass, and bone traits compared to those fed the Arg-deficient reduced protein diet supplemented with Arg.…”
Section: Introductionmentioning
confidence: 99%